64‐1: Invited Paper: Challenges for Realizing QD‐LED Display. Issue 1 (28th June 2021) - Kanehiro, Masayuki; Nakanishi, Yohei; Ishida, Takeshi; Ryowa, Tatsuya; Izumi, Makoto; Iwata, Noboru; Asaoka, Yasushi; Kamada, Tsuyoshi; Berryman-Bousquet, Valerie
Abstract : This paper reports on the potential of quantum dot light emitting diode (QD‐LED) as a future display technology and on the advances required to realize it. We give an update on development of QD materials, lifetime and UV lithography‐based fabrication process for active matrix QD‐LED displays.